The Influence of Good Corporate Governance, Corporate Social Responsibility and Free Cash Floe on Financial Performance and Company Value: Pengaruh Good Corporate Governance, Corporate Social Responsiblity Dan Free Cash Floe Terhadap Kinerja Keuangan Dan Nilai Perusahaan - Rizqi Silviati; Hadiah Fitriyah (Academia Open, 2021)
Financial performance is the company's ability to manage and control its resources, which is reflected in the financial statements proxied by ROA. Firm value is the level of success of the company in developing the company which is reflected in the share price proxied by PBV. The purpose of this study was to analyze the effect of the independence of the board of commissioners, audit committee, corporate social responsibility and free cash flow on financial performance and firm value. In this study, the population used is a food and beverage sub-sector manufacturing company listed on the Indonesia Stock Exchange in 2014 – 2018 with a total sample of 11 companies. The results of this study show that the results of the independence of the board of commissioners and the audit committee have no significant effect on financial performance, while Corporate Social Responsibility and free cash flow have a significant effect on financial performance. Meanwhile, the independence of the board of commissioners and corporate social responsibility have a significant effect on firm value, while the audit committee and free cash flow have no effect on firm value.